Anticancer perspective of 6-shogaol: anticancer properties, mechanism of action, synergism and delivery system - Yaoxia Jia; Xing Li; Xiangqi Meng; Jinjie Lei; Yangmiao Xia; Lingying Yu (BMC, 2023)
Abstract Cancer is a malignant disease that has plagued human beings all the time, but the treatment effect of commonly used anticancer drugs in clinical practice is not ideal by reason of their drug tolerance and Strong adverse reactions to patients. Therefore, it is imperative to find effective and low-toxic anticancer drugs. Many research works have shown that natural products in Chinese herbal medicine have great anticancer potential, such as 6-shogaol, a monomer composition obtained from Chinese herbal ginger, which has been confirmed by numerous in vitro or vivo studies to be an excellent anti-cancer active substance. In addition, most notably, 6-shogaol has different selectivity for normal and cancer cells during treatment, which makes it valuable for further research and clinical development. Therefore, this review focus on the anti-cancer attributes, the mechanism and the regulation of related signaling pathways of 6-shogaol. In addition, its synergy with commonly used anticancer drugs, potential drug delivery systems and prospects for future research are discussed. This is the first review to comprehensively summarize the anti-cancer mechanism of 6-shogaol, hoping to provide a theoretical basis and guiding significance for future anti-cancer research and clinical development of 6-shogaol. Graphical Abstract